Evaluation of Antioxidant and Antitumor Activities of Wrightia arborea - Ronok Zahan,; Laizuman Nahar,; Ashik Mosaddik,; Mohammad Abdur Rashid,; Amir Hassan ,; Mansoor Ahmed, (Journal of Basic & Applied Sciences, 2021)
Wrightia arborea (Br.) (Family-Apocynaceae), locally known as Sathkurchi, is a small deciduous tree with small branches and densely velvety leaves. This study was designed to investigate the antioxidant and anti tumor activities of leaves of W. arborea. Antioxidant potential was evaluated in vitro by DPPH (1,1-diphenyl-2-picrylhydrazyl) scavenging- and reducing power- assay method which was concentration dependent that was 25-200 µg/ml. The extract showed scavenging activity with IC50 value of 15.23 ± 4.10 µg/ml for DPPH and also showed reducing activity in dose dependent manner. In addition, total phenol and flavonoid content were determined by Folin-Ciocalteu reagent and were found to be 112.54 ± 9.74 mg/g plant extract (in GAE) and 247.14 ± 15.45 mg/g plant extract (in quercetin equivalent), respectively. The antioxidant capacity was evaluated by phosphomolybdenum method and was found to be 117.27 ± 12.36 mg/g plant extract (in ascorbic acid equivalents). The anti tumor effect of the methanol extractwas determined with doses of 5, 10 and 20 mg/kg b.wt against Ehrlich ascites carcinoma (EAC) in mice with respect to the determination of tumor volume, tumor weight, % of cell growth inhibition, % increase in life span (%ILS), and hematological parameter (WBC, RBC and hemoglobin). The methanol extract of W. arborea decreased the tumor weight significantly compared to control group at all the mentioned doses and the highest was observed at the dose of 20 mg/kg b. wt. (1.28 ± 0.15 g). The % of cell growth inhibition increased in dose dependent manner like 36.43 ± 7.45, 58.76 ± 9.43 and 98.43 ± 12.45 at the doses of 5, 10, 20 mg/kg b.wt. respectively. The %ILS was also enhanced in all the doses where 20 mg/kg b.wt showed maximum effect (105.5 ± 3.57). Heamoglobin (Hb) content was significantly increased 8.12 ± 2.6, 10.23 ± 1.62 and 12.12 ± 2.09 g/dL at the doses of 5, 10 and 20 mg/kg b.wt. respectively, compared to EAC control mice (4.95 ± 1.80 g). There was a significant (p< 0.05, p< 0.01, p<0.001) decrease in RBC count and increase in WBC counts in extract treated animals when compared to EAC control animals. This is the first report of biological activities of leaves of W. arborea and it showed significant antioxidant as well as antitumor activity.